Withania somnifera (Indian ginseng) in diabetes mellitus: A systematic review and meta‐analysis of scientific evidence from experimental research to clinical application. (23rd January 2020) - Durg, Sharanbasappa; Bavage, Sachin; Shivaram, Shivakumar B.
Abstract : Withania somnifera Dunal, also known as Indian ginseng, has been in use since ancient times in the management of diabetes mellitus (DM). This systematic review and meta‐analysis evaluated the efficacy/effectiveness, safety and tolerability of W. somnifera in managing DM. Literature search (published/unpublished) was performed from inception to April 2019 in guidelines recommended databases. A total of 6 in‐vitro, 13 pre‐clinical and 5 clinical studies were included for systematic evaluation. W. somnifera treatment in DM significantly restored the altered levels of blood glucose (experimental data; mean difference, −196.27; 95% confidence interval [−220.96, −171.58]; p  < .00001) glycosylated haemoglobin (HbA1c), insulin, lipid profile, serum and oxidative stress markers with no safety concerns. The results suggest the potential role of W. somnifera in managing DM. However, the available clinical data are not considerably enough to provide novel and sufficiently robust evidence for the use of W. somnifera in managing DM. To further strength the anti‐diabetic profile of W. somnifera, well‐designed randomized‐controlled trial(s) with a larger sample size and longer duration is warranted with evaluation of its effect primarily on blood glucose, HbA1c and insulin. Future research also needs to elucidate the molecular mechanism(s) of W. somnifera including its active principles in DM.